Common Stock Price Volatility Measures and Patterns - Altman, Edward I.; Schwartz, Robert A. (Journal of Financial and Quantitative Analysis, 1970)
This study is another attempt to analyze the behavior of common stock prices. In the last decade, and even before that, literature has spewed forth an abundant supply of studies in this area, from random walkers, to optimum portfolioers, to performance measurers. Terms such as risk and return, variance and covariance, and variability and volatility proliferate journal pages and our daily conversations.